Legality Of Authentic Deed With Cyber Notary Basis According To Legal Assurance Principles - Mutiaratu Astari Rafli (Faculty of Law, University of Mataram, 2022)
Cyber Notary is a concept that uses technological advancements to allow notaries to perform their daily duties by creating authentic deeds in cyberspace. Notaries require legal certainty in order to complete the electronic deed with the goal of serving as a guide. This study aims to determine the shape of the legality of making an authentic deed with a cyber notary basis according to legal certainty principles. The type of research used in this research is normative juridical, namely the approach method that uses the positivist legislative conception. The results of this study are Cyber ​​notary does not meet criteria number five of the principle of legal certainty and in fact the cyber notary is still contrary to the legality of the proof of law.